Influence Of Electronic Word Of Mouth On Purchase Intention Of Consumer Durable Goods (Journal of Namibian Studies : History Politics Culture, 2023)
Social media and electronic word of mouth have completely changed the way information and experiences are communicated effectively. In a changing marketing environment, it has become a business strategy. Through electronic word of mouth, consumers can express their ideas and experiences about products and services to other consumers due to the growth of the Internet and advances in information and communication technologies. An effort has been made to study how purchase intentions of consumer durable goods in Cuddalore district are influenced by electronic word of mouth. Multistage sampling technique was used to collect primary data for the study. Of the seven taluks in Cuddalore district, five have been chosen for the first stage. 450 respondents were chosen for the second stage by convenience sampling. This empirical study was conducted using a survey method. The primary data, which constitutes an essential part of the study, was collected using a schedule from 450 respondents. A schedule was developed using the Likert scale technique while taking into account the objectives of the study. To assess the relevance of the questions, a pre-test of the schedule was carried out with 25 consumers. Necessary corrections have been made to the revised schedule in light of the pre-testing. Secondary data came from theses, journals, periodicals and unpublished books. The results revealed that the top five factors that influenced consumers' intentions to purchase durable goods were homophily, product nature, EWOM quality, EWOM volume and credibility of the product. On the other hand, the least important factors affecting buyers' intentions to purchase durable goods are website type, link strength, and reviewer expertise. The researcher suggested measures to improve the effectiveness of electronic word of mouth.